2022
DOI: 10.1093/nargab/lqac031
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific de novo gene birth revealed by presence–absence variant genes in Caenorhabditis elegans

Abstract: Genes embed their evolutionary history in the form of various alleles. Presence–absence variants (PAVs) are extreme cases of such alleles, where a gene present in one haplotype does not exist in another. Because PAVs may result from either birth or death of a gene, PAV genes and their alternative alleles, if available, can represent a basis for rapid intraspecific gene evolution. Using long-read sequencing technologies, this study traced the possible evolution of PAV genes in the PD1074 and CB4856 C. elegans s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Indeed, even though TE insertions are not the main events enabling neORF emergence, their presence in genomes may promote other mutations that contribute to neORFs emergence. This has also been suggested by ( Lee et al 2022 ), who studied presence-absence variants of genes in C.elegans , and showed that some of these de novo genes have signatures of active transposons. Concerning the 25%–30% of neORFs which emerged inside TEs, the question is whether to consider them as de novo genes.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, even though TE insertions are not the main events enabling neORF emergence, their presence in genomes may promote other mutations that contribute to neORFs emergence. This has also been suggested by ( Lee et al 2022 ), who studied presence-absence variants of genes in C.elegans , and showed that some of these de novo genes have signatures of active transposons. Concerning the 25%–30% of neORFs which emerged inside TEs, the question is whether to consider them as de novo genes.…”
Section: Discussionsupporting
confidence: 64%
“…These include Illumina paired-end data of over 600 wild isolates by CeNDR, which also obtained first-generation PacBio long-read data of 14 wild isolates. Second-generation PacBio HiFi data 20 and Oxford Nanopore Technologies (ONT) long-read data 21 are available with CB4856 HA from Hawaii, which is the most intensively studied C. elegans wild isolate aside from the standard wild type strain N2. Illumina, PacBio, and ONT data is available with an N2-derivative with no known history of mutagenesis called VC2010 or PD1074 22 , 23 and is called CGC1 at Caenorhabditis elegans genetics center.…”
Section: Resultsmentioning
confidence: 99%
“…Long-read DNA sequencing and short-read RNA sequencing of LJ2284, LJ2285, LJ2400, and LJ2406 were conducted as previously described ( Kim et al 2019a ; Lee et al 2022a ). In summary, genomic DNA was extracted from mixed-stage worms using phenol/chloroform/isoamyl alcohol (25:24:1) and sequenced using the HiFi mode of the PacBio Sequel II platform by Macrogen.…”
Section: Methodsmentioning
confidence: 99%